Protective effect of Agrimonia pilosa polysaccharides on dexamethasone‐treated MC3T3‐E1 cells via Wnt/β‐Catenin pathway. Issue 3 (19th January 2020) - Huang, Wei; Jin, Shengyang; Yang, Wenbo; Tian, Shuo; Meng, Chunqing; Deng, Huan; Wang, Hong
Abstract: A water‐soluble polysaccharide (APP‐AW) was isolated from Agrimonia pilosa and prepared to three sulphated derivatives (S1, S2 and S3). The results showed that pre‐treatment with APP‐AW, S1, S2 and S3 each at the concentration of 50 μg/mL for 48 hours was able to prevent cytotoxicity induced by 1 μmol/L dexamethasone (Dex) in MC3T3‐E1 cells via inhibition of apoptosis, which is in line with the findings in flow cytometry analysis. Meanwhile, the decreased ALP activity, collagen content, mineralization, BMP2, Runx2, OSX and OCN protein expression in DEX‐treated MC3T3‐E1 cells were reversed by the addition of APP‐AW, S1, S2 and S3. Moreover, APP‐AW, S1, S2 and S3 rescued DEX‐induced increase of Bax, cytochrome c and caspase‐3 and decrease of Bcl‐2, Wnt3, β‐catenin and c‐Myc protein expression in MC3T3‐E1 cells. Our findings suggest that pre‐treatment with APP‐AW, S1, S2 and S3 could significantly protect MC3T3‐E1 cells against Dex‐induced cell injury via inhibiting apoptosis and activating Wnt/β‐Catenin signalling pathway, thus application of these polysaccharides may be a promising alternative strategy for steroid‐induced avascular necrosis of the femoral head (SANFH) therapy.